RHIZOBAKTERIA PENGHASIL FITOHORMON IAA PADA RHIZOSFIR TUMBUHAN SEMAK KARAMUNTING, TITONIA, DAN TANAMAN PANGAN - Agustian Agustian; Nuriyani Nuriyani; Lusi Maira; Oktanis Emalinda (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2010)
Rhizobacteria from various research results have shown an important role in producing organic compounds (phytohormone) which can affect plant physiological processes even in low concentrations. This research aimed to study the production of Indole Acetic Acid (IAA) in several plants rhizosphere, to calculate the rhizobacteria population that able to produce and synthesize IAA and to isolate these rhizobacteria from several rhizospheres of cultivated plants (maize and peanut) and bush plant i.e. karamunting (Rhodomyrtus tomentosa) and titonia (Tithonia diversifolia). All plants and crops were obtained from experimental station Faculty of Agriculture Andalas University. Further research is conducted in Soil Biology Laboratory Faculty of Agriculture. Experimental design in this study was not used but the data obtained from 3 replications tested by T test at 5% level and if it was significantly different it would be followed by further HSD tests at 5% level. Highest content of IAA was found in the peanut crop (67.30 ppm), followed by maize (53.61 ppm) and 28.53 ppm for titonia. Whereas the lowest content of IAA was found in karamunting rhizosphere, it was 22.29 ppm. The highest amount of rhizobacteria was obtained from peanut rhizosphere followed by maize and titonia i.e 18.28, 12.08 and 7.87% of the total population, respectively. There was no IAA producing rhizobacteria population was found in karamunting rhizosphere. Based on the results of the ability of the test to produce IAA in the King’s B liquid medium at low pH (pH 4.0), the leading isolates were obtained in each rhizosphere, namely: J.2b and J.3b isolates from maize rhizosphere; Kc.1b, Kc.2b and Kc.3b from peanut isolates, and Ti.3c isolates from titonia rhizosphere.Key words : Rhizobacteria, IAA, Rhodomyrtus tomentosa, Tithonia diversifolia, peanut and maize